Dream incorporation of three different bodily stimuli - Emma Peters; Xinlin Wang; Martin Dresler; Daniel Erlacher (Bern Open Publishing, 2024)
Introduction Lucid dreaming opens the possibility to rehearse sport skills within a dream while sleeping (Peters et al. 2023; Stumbrys et al. 2016). But so far, no induction techniques have been developed to induce reliable lucid dreams. One potential technique is to apply external stimulation while a person is sleeping in order to send a hint into the dream which might enhance lucidity in the ongoing dream. Several studies have tested dream incorporation rates (DIR) with different stimuli and different results (Schredl, 2018), but none with a larger sample size and a within-design. Furthermore, in this study we wanted to explore body related stimulations to evoke in future studies lucid dreams. Methods 10-Channel polysomnography and three different bodily stimulation methods were combined during three consecutive test nights with each night using one stimulation method (plus adaptation night). The three stimulation methods consisted of electrical forearm muscle stimulation (EMS), galvanic vestibular stimulation (GVS), and haptic vibration stimulation (HS). During REM sleep, one of the three stimuli was presented or a sham condition was applied in a counterbalanced order. The stimuli were followed by REM awakenings, resulting in corresponding verbal dream reports. With the help of those reports, the translation from a physical arm movement, vestibular sensation and vibration into the dream environment was investigated using dream content analysis. Movement of the dream arm, balance related activity and tactile or somatosensory sensations targeted the dream incorporations of EMS, GVS and HS respectively. Results Movement of the arm was present in 23.2%, 8.1% and 23.5% of EMS, GVS and HS dreams respectively. Balance-related activity was present in 6.1%, 7.9% and 5.8% of EMS, GVS and HS dreams respectively. Finally, tactile and somatosensory sensations were present in 13.6%, 0% and 6.3% of the EMS, GVS and HS dreams respectively. After correcting for sham condition, tactile and somatosensory sensations on the EMS dreams seem to be the strongest incorporation effect upon stimulation. Discussion/Conclusion We tested dream incorporation of three different stimulation methods using a within-design on a larger sample size, a method that has never been attempted before. GVS appears unsuccessful in altering dream content, but this might be confounded due to challenges in methodology. EMS evokes the most dream incorporation in the scale of tactile and somatosensory dream content followed by HS. The investigation of the incorporation of external kinesthetic stimulation into dream content represents a fundamental contribution to various scientific fields and could foster future research on lucid dream induction, enabling the further exploration of sport practice in a sleep state. References Peters, E., Golembiewski, S., Erlacher, D., & Dresler, M. (2023). Extending mental practice to sleep: Enhancing motor skills through lucid dreaming. Medical Hypotheses, 174, Article 111066. https://doi.org/10.1016/j.mehy.2023.111066 Schredl, M. (2018). Researching Dreams: The Fundamentals. Springer International. https://doi.org/10.1007/978-3-319-95453-0 Stumbrys, T., Erlacher, D., & Schredl, M. (2016). Effectiveness of motor practice in lucid dreams: A comparison with physical and mental practice. Journal of Sports Sciences, 34(1), 27-34. https://doi.org/10.1080/02640414.2015.1030342